The prevalence of depression among elderly patients attending primary care clinics in Kuantan, Pahang, Malaysia - Md Aris, Mohd Aznan; Samsuddin, Niza (2009)
Identifying factors associated with depression among elderly population is important in order to improve their quality of life. A cross sectional study was conducted among elderly in three primary care clinics, Kuantan, Pahang in assessing the depression and its associated factors. The respondents were selected through convenient sampling and interviewed by using reconstruct standardized questionnaire which includes social-demographic background, medical illness, ability to perform basic activities of daily living (ADL), cognitive function and depression assessment. Out of 600 elderly that attended the clinics from 1st December 2006 to 31st January 2007, 182 (30.3%) respondents agreed to enroll in the study. The respondents comprised of Malay (93.4%), females (54.4%) and married (71.4%) elderly. Most of them were living with their family (92.3%), received formal education background (64.8%), had no past history of hospital admission (81.3%) and median income per capita of RM250 per month. Most respondents (90.7%) suffered from chronic illness, 19.8% were functional dependent (according to Barthel index), 15.4% had cognitive impairment (according ECAQ) and 17.0% had depression (according to GDS-14). The study revealed that depression were found significantly difference with increasing age, marital status, occupation, living arrangements, history of hospital admission and presence of cognitive impairment. These findings highlighted that high prevalence of elderly attended the primary care clinics have a depression that require greater in health intervention by healthcare professionals.